Some like it tailor-made: The effectiveness of personalized coupons for lower-calorie food choices at a university canteen - Minh T. T. Nguyen; Agnes Emberger-Klein; Klaus Menrad (International Journal of Consumer Studies, 2021)
As an emerging marketing tool that targets shoppers individually based on their purchase histories, personalized price promotion is likely to address the limitations of untargeted price reductions. However, there is no prior evidence to support the effectiveness of this approach in promoting low-calorie food choices, and which consumer-specific characteristics influence its performance. In this study, we analyze the effectiveness of personalized and non-personalized coupons for lower-calorie menus at a university canteen. In addition, we examine the interaction between psychological factors and promotional responses, as well as subsequent dietary outcomes. Overall, personalized price promotion performs better than the untargeted approach in encouraging shoppers to redeem the offered coupons and make menu choices with more healthy items and fewer calories. Factors such as calorie concerns, convenience orientation, and the resistance to change eating habits have significant effects on coupon redemption. The role of coupon redemption in mediating the association between such psychological predictors and dietary changes proves the effectiveness of price reductions. This study highlights the potential of personalized price promotion as a healthy eating intervention and sets the groundwork for developing and evaluating this instrument.
Keywords: 330; food away from home; healthy eating intervention; lower-calorie food; personalized price promotion; price reduction